Teologis atau Politis? Pencarian Makna Pergulatan Historis dalam Pengakuan Iman Nicea-Konstantinopel - Radius Aditiya Jonar (Theologia in Loco, 2020)
Nicene-Constantinople creed is usually understood only as a result of theological opinion struggle from our church fathers in the past and ignored political power that influenced it. Collaboration between theological opinion and political power in making process has made Nicene-Constantinople creed become unique and makes us as modern church generations in this day need to question the meaning of the present political power that usually influences church decisions to give benefit for their political interest.